Predicting the indication for adjuvant radiation therapy according to EAU guidelines among patients with high-risk prostate cancer: a novel multivariable model : clinical research - Siech, Carolin; von Kriegstein, Helge; Wenzel, Mike; Cano Garcia, Cristina; Le, Quynh Chi; Tennstedt, Pierre; Preißer, Felix; Maurer, Tobias; Kriegmair, Maximilian; Chun, Felix K. H.; Graefen, Markus; Tilki, Derya; et al. (Prostate cancer and prostatic diseases, 2025)
To develop a novel model for preoperatively predicting the indication for adjuvant radiation therapy after radical prostatectomy according to current guideline recommendations of the European Association of Urology (EAU) based on patient and clinical tumor characteristics in high-risk prostate cancer patients.
Gesehen am 30.10.2025